Firm heterogeneity, contract enforcement, and the industry dynamics of offshoring - Gianmarco I. P. Ottaviano; Alireza Naghavi (Fondazione Eni Enrico Mattei (FEEM), 2009)
We develop an endogenous growth model to study the long run consequences of offshoring with firm heterogeneity and incomplete contracts. In so doing, we model offshoring as the geographical fragmentation of a firm's production chain between a home upstream division and a foreign downstream one. On the positive side, we show that, when contracts are incomplete, the possibility of offshoring has favorable implications for economic growth. Yet, offshoring induced by a higher bargaining power of the upstream division can hamper growth: while there is always a positive correlation between upstream bargaining weight and offshoring activities, there is a non-monotonic relationship between these and growth. Whether offshoring with incomplete contracts also increases consumption depends on firm heterogeneity. On the normative side, we show that, whereas with complete contract efficiency is restored through a subsidy to R&D only, with incomplete contracts a production subsidy to offshored upstream divisions is needed too.
Keywords: D23; F23; L23; O31; O43; 330; Offshoring; Heterogeneous Firms; Incomplete Contracts; Growth; Industry Dynamics